The Epidemiology of Chlamydia trachomatis Organism Load During Genital Infection: A Systematic Review. (9th December 2014) - Vodstrcil, Lenka A.; McIver, Ruthy; Huston, Wilhelmina M.; Tabrizi, Sepehr N.; Timms, Peter; Hocking, Jane S.
Abstract: Background.  The role of organism load in Chlamydia trachomatis infection is not well understood. We conducted a systematic review to investigate the epidemiology of C. trachomatis organism load in human genital chlamydia infection. Methods.  Embase, PubMed, and Medline databases were searched for literature published through August 2014. English-language publications that quantified load in humans were eligible. Participant characteristics and laboratory data were extracted. Results.  A total of 737 records were identified, and 29 publications involving 40 883 participants were included. In women, load was highest for cervical swabs and lowest for urine specimens. In men, load was highest for rectal swabs and similar for urethral swabs and urine specimens. Evidence of any association between load and age, serovar, risk of transmission, hormone levels, and concurrent sexually transmitted infections was inconsistent. Eight of 9 culture-based studies found an association between load and signs and symptoms, in contrast with only 3 of 8 nucleic acid amplification test (NAAT)-based studies ( P = .03). Conclusion.   Chlamydia organism load varies by specimen type and site of sampling, and viable chlamydia organism load may be a more important indicator of severity of infection than total load measured by NAAT.